PENGARUH KEPEMILIKAN KAS, RASIO PEMBAYARAN DIVIDEN, RISIKO KEUANGAN, KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PERATAAN LABA (Studi Empiris pada Perusahaan Sektor Consumer Cyclicals dan Consumer Non-Cyclicals yang Terdaftar di BEI Periode 2020-2023) - Callasaro Sispa; Darsono Darsono (Diponegoro Journal of Accounting, 2025)
Income smoothing is a form of earnings management conducted to reduce fluctuations in reported earnings in order to achieve more stable profit levels. Cash holding is measured by the percentage of cash and cash equivalents, dividend payout ratio, financial risk is measured by the debt-to-asset ratio, while managerial ownership and institutional ownership are measured by the percentage of shares owned by managers and institutions. Therefore, this study aims to examine the effect of cash holding, dividend payout ratio, financial risk, managerial ownership, and institutional ownership on income smoothing.The population in this study consists of companies in the consumer cyclicals and consumer non-cyclicals sectors listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The sample was selected using purposive sampling based on specific criteria, resulting in 266 observation data. The data used are secondary data obtained from the official websites of the companies and the Bloomberg Laboratory of the FEB UNDIP as a source of financial report data. Hypothesis testing was conducted using multiple linear regression analysis with IBM SPSS software.The results of the study show that cash holding, financial risk, and managerial ownership have a positive and significant effect on income smoothing, while the dividend payout ratio and institutional ownership have no significant effect. This study aims to provide insights for companies, investors, and regulators in understanding the factors that influence income smoothing.